Human metabolism and urinary excretion kinetics of di-n-butyl adipate (DnBA) after oral and dermal administration in three volunteers. (1st June 2021) - Ringbeck, Benedikt; Bury, Daniel; Gotthardt, Alexandra; Hayen, Heiko; Otter, Rainer; Weiss, Tobias; Brüning, Thomas; Koch, Holger M.
Highlights: Oral dose of di- n -butyl adipate (DnBA) to three volunteers. Dose recoveries of four oxidized monoester metabolites 0.005−0.47 % (mean values). Dermal application of sunscreen containing DnBA (n = 3): different metabolite ratios. Excretion kinetics up to 48 h (oral) and 72 h (dermal). Simple monoester and 3-hydroxy metabolite seem specific biomarkers of exposure. Abstract: Di- n -butyl adipate (DnBA) is used as a plasticizer and in various consumer products (e.g. personal care products) replacing, in part, the endocrine disruptor di- n -butyl phthalate (DnBP). We provide quantitative in vivo data on human DnBA metabolism and excretion after oral dose (105−185 μg/kg bw) and dermal application to three volunteers each as a tool for exposure and risk assessment. Complete and consecutive urine samples were collected for two (oral) and four days (dermal), respectively, and analyzed for the metabolites mono- n -butyl adipate (MnBA), 3- and tentative 4-hydroxy-mono- n -butyl adipate (3OH-MnBA, 4OH-MnBA), and 3-carboxy-mono- n -propyl adipate (3cx-MnPrA), as well as the hydrolysis product adipic acid (AA) using stable isotope dilution quantification. Metabolites were excreted within 24 h after oral dose with one or two concentration maxima at 0.8–3.0 h (n = 3) and 4.8−6.3 h (n = 2). AA was the major but unspecific metabolite with urinary excretion fractions (FUE s) of 14−26 %. Mean FUE s (range) of 3cx-MnPrA, MnBA, 3OH-MnBA, and tentative 4OH-MnBA were low, but consistent between volunteers (0.47 % (0.35−0.63 %), 0.079 % (0.065−0.091 %), 0.012 % (0.006−0.016 %), and 0.005 % (0.002−0.009 %), respectively). MnBA and 3OH-MnBA seem to be suitable, specific exposure biomarkers for DnBA, whereas 3cx-MnPrA and 4OH-MnBA seem to originate also from other, unknown sources not related to DnBA. Compared to the oral study, metabolite excretion in the dermal study was delayed and MnBA excretion was somewhat higher compared to the oxidized metabolites. Based on urinary concentrations and the above excretion fractions, calculated uptakes in the dermal study did not exceed the adipate ester ADI of 5 mg/(kg bw*day).